Liberia : 2010 Article IV Consultation and Fifth Review Under the Three-Year Arrangement Under the Extended Credit Facility-Staff Report; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Liberia. (IMF Staff Country Reports; Country Report ;, 2010)
The post-conflict economic stabilization in Liberia is now complete. Inflation pressure is easing owing to lower fuel and food prices, and there is a rebound in exports. Sound macroeconomic policies, strengthened institutions, and debt relief have stabilized the economy and have supported confidence-building. Fiscal policies have supported the stabilization. The scope for an active monetary policy remains limited owing to high levels of dollarization and the lack of monetary instruments. The government has coped with the adverse income and investment effects of the global financial crisis.